Posyandu Cadres’ Readiness in The Implementation of Integrated Primary Health Care - Zyana Nafilul Ahsaniar; Ririn Nurmandhani; Eti Rimawati; Firmansyah Kholiq Pradana; Vilda Ana Veria Setyawati; Muhammad Iqbal (VISIKES, 2026)
The transformation of Posyandu into the Integrated Primary Health Care (ILP) model was initiated by Indonesia’s Ministry of Health to strengthen primary health care services. The success of this transformation depends on the readiness of Posyandu cadres, who act as key field implementers. This study aimed to examine the relationship between change valence and information assessment with cadre readiness in supporting ILP implementation in Banyumanik District, Semarang City. A cross-sectional quantitative study was conducted among 50 Posyandu cadres (n = 50) selected using multistage random sampling. Data were collected using a validated questionnaire and analyzed using the Chi-square test with prevalence ratio (PR) analysisA crosssectional quantitative design was employed, using a validated questionnaire distributed to 50 cadres selected through multistage random sampling. Data were analyzed using the Chi-square test. The findings showed a significant relationship between change valence and cadre readiness (p = 0.001; PR = 10.00), as well as between information assessment and readiness (p = 0.001; PR = 29.13). Cadres who had positive perceptions of change and received adequate information were more likely to be ready to implement ILP. The study recommends that local governments enhance documentation of training outcomes and that Puskesmas and Posyandu coordinators develop structured mentoring and certification systems. These efforts are crucial to improving cadre readiness and ensuring sustainable implementation of ILP at the community level.